PENGARUH REFUGIA TERHADAP INTENSITAS DAN POPULASI HAMA PENGGEREK DAUN (Spodoptera litura Hbn) PADA CABAI KERITING (Capsicum annum L) - heri haryanto (Fakultas Pertanian Universitas Mataram, 2020)
This research aims to know the effect of refugia on the intensity and population of leaf borer pests (Spodoptera litura Hbn) on chili (Capsicum annum L.) the method used the experimentalmethod that conduct experiment in the field. This research was conducted in Desember 2018 until March 2019. The design used in this research was Randomized Complete Block Design (RCBD) with 4 treatments, nomely, control, Sunflower, Marigold and Zinnia treatment repeated 3 times to obtain 60 plant samples in 12 experimental units. Observation data were analyzed by analysis of variance and test further with a Honestly Significant Difference tests at a real level of 5%. The results showed that the cause of leaf damage in the chili plant (Capsicum annum L.) was caused by the Spodoptera litura Hbn pests in each treatment. The highests percentage of domage is (4,803%) found in R0 (Control), while the lowest average persentage is (2,16%) found in R2 (Marigold) treatment. The result of the correlation regression analysis showed that intensity of the attacks caused by Spodoptera litura Hbn was 63,3 % by population of pests and 27,7% was caused by other factors.